Protein fishing from single live cells - Elaheh Shekaramiz; Rupak Doshi; H. Kumar Wickramasinghe (Journal of Nanobiotechnology, 2018)
Abstract Intracellular protein and proteomic studies using mass spectrometry, imaging microscopy, flow cytometry, or western blotting techniques require genetic manipulation, cell permeabilization, and/or cell lysis. We present a biophysical method that employs a nanoaspirator to ‘fish’ native cytoplasmic or nuclear proteins from single mammalian cells, without compromising cell viability, followed by ex cellulo quantitative detection. Our work paves the way for spatiotemporally-controlled, quantitative, live, single-cell proteomics.